Taxonomic Determination of Therapeutic Argentine Species of Ilex - Spegazzini, Etile Dolores (2002)
This is comparative study of Ilex paraguariensis St. Hil. var. paraguariensis Loes., and cogeneric Argentine adulterants: I. dumosa Reissek var. dumosa Reissek, I. dumosa var. guaranina Loes., I. brevicuspis Reissek, I. theezans Reissek and I. argentina Lillo. The anatomy and quantitative micrographic parameters (proportional magnitudes, stomata index and palisade ratio) of these leaves was studied to the establish standards in agreement with the WHO for the vegetables drugs. A micrographic parameters table is presented for control quality of the raw material, fragmentary or powdered.